High-temperature dielectric polymer as well as preparation method and application thereof

The polymerization reaction initiated by Grubbs catalyst was synthesized and ferroelectric microstructures were formed through annealing treatment, which solved the problems of low dielectric constant and poor high-temperature capacitance performance in the prior art, and achieved high storage at high temperatures Energy density and high energy storage efficiency.

CN119463132AActive Publication Date: 2025-02-18SHANGHAI JIAOTONG UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411631070.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-18
Estimated Expiration
2044-11-15

AI Technical Summary

Technical Problem

The existing non-ferroelectric polymers have low dielectric constants, and the capacitance performance of ferroelectric polymers at high temperatures is poor, which cannot meet the needs of high energy density and high temperature stability.

Method used

The open-loop metathesis polymerization reaction initiated by the Grubbs catalyst was synthesized to form a ferroelectric-like microstructure polymer with side chain dipoles facing the same direction, and annealing was used to form a ferroelectric-like microstructure, which increased the dielectric constant and low dielectric loss.

Benefits of technology

At 150°C, the dielectric constant increased from 7.5 to 12, and the dielectric loss remained below 0.02, achieving high energy storage density (10.8J/cm3) and high energy storage efficiency (>90%) at high temperatures, and at 350MV/ More than 10,000 charge-discharge cycles can be performed continuously under an electric field of m.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463132A_ABST
    Figure CN119463132A_ABST
Patent Text Reader

Abstract

The invention relates to the field of dielectric materials and energy storage materials, and discloses a high-temperature dielectric polymer and a preparation method and application thereof.The preparation method comprises the steps that 5-norbornene-2, 3-dicarboximide is subjected to a reduction reaction through lithium aluminum hydride, and a 5-norbornene-pyrrolidine intermediate is obtained; placing the intermediate and p-benzenesulfonyl chloride in a chloroform solution, and dropwise adding triethylamine for reaction; the norbornene pyrrolidine phenyl sulfone monomer is obtained; the monomer is subjected to a ring-opening metathesis polymerization reaction through a Grubbs catalyst, and polynorbornene pyrrolidine phenyl sulfone is obtained; the preparation method comprises the following steps: putting polynorbornene pyrrolidine phenylsulfone and p-toluenesulfonyl hydrazide into a toluene solution, and carrying out hydrogenation reaction to obtain a target polymer. The polymer disclosed by the invention can obtain an electric polarization energy storage density (charge and discharge efficiency gt) of about 10.8 J / cm < 3 > only by applying a low electric field intensity of 350 MV / m at 150 DEG C; 90%) over existing high temperature polymer dielectric materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of dielectric materials and energy storage materials, and in particular to a high-temperature dielectric polymer and a preparation method and application thereof. Background Art

[0002] Dielectric polymers have excellent electrical breakdown strength and ultra-high power density, and have become the preferred material for capacitor energy storage. They are widely used in high temperature environments (~150°C) such as electric vehicles, oil and gas industries, power systems, and aerospace. Biaxially oriented polypropylene (BOPP) is an ideal commercial dielectric polymer with excellent charge and discharge reliability. However, due to the low glass transition temperature of BOPP (>105°C), its energy storage performance deteriorates rapidly when the temperature is higher than its glass transition temperature. In addition, BOPP is constrained by a low dielectric constant of nearly 2.2, and its discharge energy density can only reach 4J / cm even at a high electric field of 600MV / m. 3 , this capacity cannot meet the growing demand for high energy density (electrical energy storage density >10J / cm at 90% charge and discharge efficiency at 150°C) due to the increasing miniaturization trend of electronic and electrical equipment. 3 ). Capacitive energy density of polymer dielectrics ε r and ε0 represent the dielectric constant of the polymer and the dielectric constant of vacuum (~8.85×10 -12 F / m), E represents the electric field strength applied to the polymer. Increasing the dielectric constant of the polymer increases the capacitance energy storage density under the same electric field. Therefore, ferroelectric polymers with a dielectric constant exceeding 10 have attracted considerable attention. However, the dielectric loss of ferroelectric polymers increases significantly with increasing temperature (>0.1), resulting in high residual polarization. Excessive residual polarization significantly reduces the charge and discharge efficiency of almost all ferroelectric polymers, resulting in the inability to achieve high discharge density values. In addition, ferroelectric polymers have a low Curie temperature and face potential degradation of ferroelectric properties at around 100°C, which significantly limits their application in high-temperature capacitance performance. Therefore, it remains crucial to find non-ferroelectric polymers with high dielectric constants.

[0003] Chinese patent CN113087879A discloses a high-temperature electrostatic energy storage double-chain polymer dielectric and preparation method. The disclosed polymer has a double-chain structure with a polar bridging group. The polymer film is characterized by having a dielectric constant and dielectric loss that are independent of temperature changes. However, the dielectric constant of this type of polymer remains at around 6 in the temperature range of 50°C to 150°C, resulting in a high-temperature (~150°C) electrical energy storage density of only 6 J / cm at a charge and discharge efficiency of 90%. 3, which cannot meet the growing demand for high energy density (>10J / cm 3 ), which means that there are still great limitations in its application. Summary of the invention

[0004] The present invention aims to provide a non-ferroelectric polymer with a high dielectric constant in view of the current situation that the dielectric constant of the existing non-ferroelectric polymer is low and the high-temperature capacitance performance of the ferroelectric polymer is poor. The present invention adopts a ring-opening metathesis polymerization reaction initiated by a Grubbs catalyst to synthesize a quasi-ferroelectric microstructure polymer with side chain dipoles facing the same direction; when the ambient temperature rises from 140°C to 200°C, the dielectric constant of the polymer can increase from 7.5 to 12, and the dielectric loss is still maintained below 0.02; and the high-temperature (150°C to 200°C) electrical energy storage density of the polymer film at 90% charge and discharge efficiency is only 10.8J / cm 3 .

[0005] To achieve the above object, on the one hand, the present invention provides a high temperature dielectric polymer, wherein the polymer has the general formula shown in formula (I):

[0006]

[0007] Wherein n represents the number of repeating structural units, and n is an integer greater than 200. Preferably, n is 200-800.

[0008] According to another aspect of the present invention, the present invention also provides a method for preparing a high temperature dielectric polymer, which comprises the following steps:

[0009] S1. reducing 5-norbornene-2,3-dicarboximide with lithium aluminum tetrahydride to obtain a 5-norbornene-pyrrolidine intermediate;

[0010] S2. 5-norbornene-pyrrolidine and p-toluenesulfonyl chloride are placed in a chloroform solution, and triethylamine is added dropwise to react to obtain a norbornene-pyrrolidine phenylsulfone monomer;

[0011] S3. The norbornene pyrrolidine phenyl sulfone monomer is subjected to a ring-opening metathesis polymerization reaction using a Grubbs catalyst under anhydrous and oxygen-free conditions. After terminating the reaction, the polymer product is diluted, settled, washed, and dried to obtain polynorbornene pyrrolidine phenyl sulfone;

[0012] S4. Place polynorbornene pyrrolidine phenyl sulfone and p-toluenesulfonyl hydrazide in a toluene solution and subject the mixture to a hydrogenation reaction to obtain a polymer of formula (I).

[0013] As a further preferred technical solution of the present invention, in step S3, the solvent for the ring-opening metathesis polymerization reaction is N,N-dimethylformamide, and the Grubbs catalyst is 3-phenyl-1H-indene-1-ylidene[bis(isobutylphosphine ligand)]ruthenium(II) dichloride.

[0014] As a further preferred technical solution of the present invention, in step S3, the molar ratio of the norbornene pyrrolidine phenyl sulfone monomer to the Grubbs catalyst is (200-500):1; and / or the concentration of the norbornene pyrrolidine phenyl sulfone monomer is 0.05-0.1 mol / L.

[0015] As a further preferred technical solution of the present invention, in step S3, the conditions for the ring-opening metathesis polymerization reaction are: a temperature of 30 to 50° C.; and / or a reaction time of 1 to 2 hours.

[0016] As a further preferred technical solution of the present invention, in step S3, the terminator of the ring-opening metathesis polymerization reaction is vinyl ethyl ether.

[0017] As a further preferred technical solution of the present invention, in step S4, the hydrogenation reaction temperature conditions are: temperature 120° C.; and / or reaction time 3 to 6 hours.

[0018] According to another aspect of the present invention, the present invention also provides a method for preparing a film using the above-mentioned high temperature dielectric polymer, which comprises the following steps:

[0019] A1. The polymer of formula (1) is dissolved in N,N-dimethylformamide to obtain a film-forming solution;

[0020] A2. After the film-forming liquid is evenly coated on the glass sheet, the solvent is evaporated at 25-40°C in advance, and then it is completely dried under vacuum at 80-100°C to obtain a transparent flexible film. Finally, it is annealed at 200-250°C to form a crystal of a ferroelectric microstructure.

[0021] As a further preferred technical solution of the present invention, the concentration of the membrane-forming solution is 3 to 5 wt %.

[0022] According to another aspect of the present invention, the present invention also provides a use of a high temperature dielectric polymer in an electrostatic energy storage insulating material.

[0023] Compared with the prior art, the following beneficial effects can be achieved:

[0024] 1) The polymer dielectric material of the present invention has a ferroelectric-like microstructure after annealing, and the dielectric constant reaches 7.5 before 110°C, and the dielectric constant increases to 10 as the temperature rises to 150°C; in addition, the dielectric loss of the polymer is less than 0.02 in the range of 0 to 150°C;

[0025] 2) The polymer dielectric material of the present invention has a ferroelectric-like microstructure after annealing and has an increased dielectric constant at high temperature. This means that a relatively low electric field strength is required to achieve high energy storage density at high temperatures, which is not achievable with existing linear dielectric polymers.

[0026] 2) The polymer dielectric material of the present invention only needs to be applied with a low electric field strength of 350 MV / m at 150°C to obtain a dielectric strength of about 10.8 J / cm 3 The polarization energy storage density (charge and discharge efficiency>90%) exceeds that of existing high-temperature polymer dielectric materials, while the electric field strength reported in patent CN113087879A needs to exceed 700MV / m;

[0027] 3) The polymer dielectric material of the present invention can be continuously charged and discharged for more than 10,000 times under an electric field of 350 MV / m, and the discharge energy output is greater than 10 J / cm 3 Its continuous output energy density is significantly better than the polymer reported in patent CN113087879A (~5.3J / cm 3 ). BRIEF DESCRIPTION OF THE DRAWINGS

[0028] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments.

[0029] Figure 1 is the H NMR spectrum of the norbornene pyrrolidine monomer obtained in Example 1 of the present invention;

[0030] Figure 2 is the H NMR spectrum of the polymer (I-1) obtained in Example 1 of the present invention;

[0031] Figure 3 The high-resolution transmission electron microscopy image of the polymer film obtained in Example 1 of the present invention after annealing is

[0032] Figure 4 This is a high-resolution transmission electron microscopy image of the polymer film obtained in Example 1 of the present invention before annealing;

[0033] Figure 5 is the correlation between the imaginary part of the dielectric constant of the polymer obtained in Example 1 of the present invention and the frequency;

[0034] Figure 6 is the gel permeation chromatogram of the polymers obtained in Example 1, Example 2, Example 3 and Example 4 of the present invention;

[0035] Figure 7The dielectric constant variation curves of the polymers obtained in Example 1, Example 2, Example 3 and Example 4 of the present invention at different temperatures, wherein the frequency is fixed at 10 Hz;

[0036] Figure 8 The dielectric loss curves of the polymers obtained in Examples 1, 2, 3 and 4 of the present invention at different temperatures are shown, wherein the frequency is fixed at 10 Hz;

[0037] Fig. 9 Graphs showing energy storage density of polymers obtained in Examples 1, 2, 3 and 4 of the present invention;

[0038] Fig.10 1 is a charge-discharge cycle diagram of the polymers obtained in Examples 1, 2, 3 and 4 of the present invention.

[0039] The purpose, features and advantages of the present invention will be further described with reference to the accompanying drawings in conjunction with the embodiments. DETAILED DESCRIPTION

[0040] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.

[0041] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The test reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the experimental methods, unless otherwise specified, are all conventional methods.

[0042] Example 1

[0043] This embodiment provides a high temperature dielectric polymer, the structure of which is shown in formula (I-1):

[0044] Where n is 200.

[0045] The steps for preparing the polymer of formula (I-1) and its film, and the electrode based on the film are as follows:

[0046] S1. Synthesis of 5-norbornene-pyrrolidine intermediate

[0047] Add 1.6 g of 5-norbornene-2,3-dicarboximide, 0.8 g of lithium aluminum tetrahydride and 50 ml of tetrahydrofuran into a 250 ml three-necked flask. React for 12 hours. After the reaction, add 1 mL of water to the reaction solution, filter the filtrate, remove the solvent from the filtrate in vacuo, recrystallize in 20 ml of ethanol, and dry in an oven at 30 ° C to obtain 5-norbornene-pyrrolidine intermediate with a yield of about 95%.

[0048] S2. Synthesis of norbornene pyrrolidine phenyl sulfone monomer

[0049] 1.5 g of 5-norbornene-pyrrolidine intermediate and 1.2 g of benzenesulfonyl chloride were added to a 100 mL round-bottom flask, 50 mL of chloroform solution and 10 mL of triethylamine were added, and then the temperature was raised to 50 ° C and reacted for 12 hours. After the reaction, the solvent was removed in vacuo, the solid was washed with deionized water, and dried in an oven at 30 ° C to obtain a norbornene pyrrolidine phenyl sulfone monomer (H NMR spectrum as Figure 1 ), yield 90%.

[0050] S3. Synthesis of polynorbornene pyrrolidine phenyl sulfone

[0051] Add 178 mg (0.2 mmol) of norbornene pyrrolidine phenyl sulfone monomer to a 250 mL reaction tube, dissolve it with 40 mL of 4,4-diaminodiphenylmethane, freeze it with liquid nitrogen, and replace it with nitrogen three times. After thawing, add Grubbs catalyst, 3-phenyl-1H-inden-1-ylidene [bis (isobutylphosphine ligand)] ruthenium (II) dichloride (3.6 mg, 0.004 mmol) to the reaction tube under nitrogen atmosphere, and carry out ring-opening metathesis polymerization at 30 ° C for 2 hours, and then add 0.5 mL of vinyl ethyl ether as a terminator. The reaction should be concentrated to 5 mL, precipitated to the bottom in 100 mL of ethanol, and centrifuged to obtain a polymer solid polynorbornene pyrrolidine phenyl sulfone, and finally washed with ethanol three times, with a yield of 94%.

[0052] S4. Synthesis of target polymer I-1

[0053] 178 mg (0.2 mmol) of polynorbornene pyrrolidine phenyl sulfone and 207 mg (0.4 mmol) of p-toluenesulfonyl hydrazide were added to a 250 mL reaction tube, heated to 120° C., and reacted for 6 hours to obtain the target polymer with a yield of 90%.

[0054] The H NMR spectrum of polymer I-1 is as follows Figure 2 As shown, the successful synthesis of this polymer (n=200) was demonstrated.

[0055] S5. Preparation of target polymer I-1 film

[0056] 100 mg of polymer was dissolved in 2.5 mL of N, N-diformamide solution (i.e., the solution concentration was 5 wt%) and evenly coated on quartz glass through a 400 μm thick four-sided preparation device. It was placed in an oven and vacuum dried at 40°C for 2 hours to remove most of the N, N-diformamide solution. The temperature was then raised to 100°C and vacuum dried for 10 to 12 hours to obtain a transparent flexible film. Its high-resolution transmission electron microscopy image is shown in the figure below. Figure 4 shown.

[0057] S6. Construction of ferroelectric-like microstructures

[0058] The obtained polymer I-1 film was placed in an oven at 220°C for 2 hours and then annealed at a rate of 1°C per minute to form a crystal of a ferroelectric microstructure. The high-resolution transmission electron microscopy image is shown in FIG. Figure 3 shown.

[0059] Figure 3 The measured polymer has a crystalline lattice, and the lattice is anisotropic, proving the formation of a ferroelectric-like microstructure; Figure 4 The measured polymer has an amorphous structure, proving that the polymer without annealing treatment has an amorphous microstructure. Figure 5 is the frequency dependence of the imaginary part of the dielectric constant of polymer I-1, Figure 5 a and Figure 5 b represents polymer I-1 without ferroelectric microstructure and with ferroelectric microstructure respectively. Relaxation peak A and relaxation peak B are the relaxation of polarization motion of phenylsulfone group at high temperature and low temperature respectively. The polymer with ferroelectric microstructure has relaxation peak A at high temperature, indicating that the polarization strength of phenylsulfone group is enhanced at high temperature, proving that the dielectric constant can be further increased at high temperature.

[0060] S7. Preparation of electrodes

[0061] Based on a magnetron sputtering coating machine, the coating machine current was set to 135A, the electroplating time was 5 minutes, and circular gold electrodes (thickness of about 100 nm, diameter of 1 cm) were plated on the upper and lower surfaces of the crystallized polymer I-1 film.

[0062] Example 2

[0063] This embodiment provides a high temperature dielectric polymer, whose structure is shown in formula (I-2):

[0064] Where n is 350.

[0065] The steps for preparing the polymer of formula (I-2) and its film, and the electrode based on the film are as follows:

[0066] S1. Synthesis of 5-norbornene-pyrrolidine intermediate

[0067] Same as Example 1.

[0068] S2. Synthesis of norbornene pyrrolidine phenyl sulfone monomer

[0069] Same as Example 1.

[0070] S3. Synthesis of polynorbornene pyrrolidine phenyl sulfone

[0071] Add 178 mg (0.2 mmol) of norbornene pyrrolidine phenyl sulfone monomer to a 250 mL reaction tube, dissolve it with 40 mL of 4,4-diaminodiphenylmethane, freeze it with liquid nitrogen, and replace it with nitrogen three times. After thawing, add Grubbs catalyst, 3-phenyl-1H-inden-1-ylidene [bis (isobutylphosphine ligand)] ruthenium (II) dichloride (2.52 mg, 0.0028 mmol) to the reaction tube under nitrogen atmosphere, and carry out ring-opening metathesis polymerization at 30 ° C for 2 hours, and then add 0.5 mL of vinyl ethyl ether as a terminator. The reaction should be concentrated to 5 mL, precipitated to the bottom in 100 mL of ethanol, centrifuged to obtain a polymer solid, and washed with ethanol three times, with a yield of 91%.

[0072] S4. Synthesis of target polymer I-2

[0073] 178 mg (0.2 mmol) of polynorbornene pyrrolidine phenyl sulfone and 207 mg (0.4 mmol) of p-toluenesulfonyl hydrazide were added to a 250 mL reaction tube, heated to 120° C., and reacted for 6 hours to obtain the target polymer with a yield of 90%.

[0074] S5. Preparation of target polymer I-2 film

[0075] Same as Example 1.

[0076] S6. Construction of ferroelectric-like microstructures

[0077] Same as Example 1.

[0078] S7. Preparation of electrodes

[0079] Same as Example 1.

[0080] Example 3

[0081] This embodiment provides a high temperature dielectric polymer, whose structure is shown in formula (I-3):

[0082] Where n is 500.

[0083] The steps for preparing the polymer of formula (I-3) and its film, and the electrode based on the film are as follows:

[0084] S1. Synthesis of 5-norbornene-pyrrolidine intermediate

[0085] Same as Example 1.

[0086] S2. Synthesis of norbornene pyrrolidine phenyl sulfone monomer

[0087] Same as Example 1.

[0088] S3. Synthesis of polynorbornene pyrrolidine phenyl sulfone

[0089] Add 178 mg (0.2 mmol) of norbornene pyrrolidine phenyl sulfone monomer to a 250 mL reaction tube, dissolve it with 40 mL of 4,4-diaminodiphenylmethane, freeze it with liquid nitrogen, and replace it with nitrogen three times. After thawing, add Grubbs catalyst, 3-phenyl-1H-inden-1-ylidene [bis (isobutylphosphine ligand)] ruthenium (II) dichloride (1.44 mg, 0.0016 mmol) to the reaction tube under nitrogen atmosphere, and carry out ring-opening metathesis polymerization at 30 ° C for 2 hours, and then add 0.5 mL of vinyl ethyl ether as a terminator. The reaction should be concentrated to 5 mL, precipitated to the bottom in 100 mL of ethanol, centrifuged to obtain a polymer solid, and washed with ethanol three times, with a yield of 97%.

[0090] S4. Synthesis of target polymer I-3

[0091] 178 mg (0.2 mmol) of polynorbornene pyrrolidine phenyl sulfone and 207 mg (0.4 mmol) of p-toluenesulfonyl hydrazide were added to a 250 mL reaction tube, heated to 120° C., and reacted for 6 hours to obtain the target polymer with a yield of 90%.

[0092] S5. Preparation of target polymer I-3 film

[0093] Same as Example 1.

[0094] S6. Construction of ferroelectric-like microstructures

[0095] Same as Example 1.

[0096] S7. Preparation of electrodes

[0097] Same as Example 1.

[0098] Example 4

[0099] This embodiment provides a high temperature dielectric polymer, whose structure is shown in Formula I-4:

[0100] Where n is 800.

[0101] The steps for preparing the polymer of formula (I-4) and its film, and the electrode based on the film are as follows:

[0102] S1. Synthesis of 5-norbornene-pyrrolidine intermediate

[0103] Same as Example 1.

[0104] S2. Synthesis of norbornene pyrrolidine phenyl sulfone monomer

[0105] Same as Example 1.

[0106] S3. Synthesis of polynorbornene pyrrolidine phenyl sulfone

[0107] Add 178 mg (0.2 mmol) of norbornene pyrrolidine phenyl sulfone monomer to a 250 mL reaction tube, dissolve it with 40 mL of 4,4-diaminodiphenylmethane, freeze it with liquid nitrogen, and replace it with nitrogen three times. After thawing, add Grubbs catalyst, 3-phenyl-1H-inden-1-ylidene [bis (isobutylphosphine ligand)] ruthenium (II) dichloride (0.9 mg, 0.001 mmol) to the reaction tube under nitrogen atmosphere, and carry out ring-opening metathesis polymerization at 30 ° C for 2 hours, and then add 0.5 mL of vinyl ethyl ether as a terminator. The reaction should be concentrated to 5 mL, precipitated to the bottom in 100 mL of ethanol, centrifuged to obtain a polymer solid, and washed with ethanol three times, with a yield of 85%.

[0108] S4. Synthesis of target polymer I-4

[0109] 178 mg (0.2 mmol) of polynorbornene pyrrolidine phenyl sulfone and 207 mg (0.4 mmol) of p-toluenesulfonyl hydrazide were added to a 250 mL reaction tube, heated to 120° C., and reacted for 6 hours to obtain the target polymer with a yield of 90%.

[0110] S5. Preparation of target polymer I-4 film

[0111] Same as Example 1.

[0112] S6. Construction of ferroelectric-like microstructures

[0113] Same as Example 1.

[0114] S7. Preparation of electrode of target polymer I-4 film

[0115] Same as Example 1.

[0116] The polymers prepared in Examples 1-4 above were characterized: Figure 6 The gel permeation chromatography of polymer I-1, I-2, I-3 and I-4 samples showed that the molecular weights were 96.2 kg / mol, 157.2 kg / mol, 239.4 kg / mol and 380.1 kg / mol, respectively. The number of structural units n of polymers I-1, I-2, I-3 and I-4 was calculated to be approximately 200, 350, 500 and 800, respectively. Figure 7 is the dielectric constant of polymer samples I-1, I-2, I-3 and I-4. It can be seen that the dielectric constant increases from 7.5 to 10 at 10 Hz in the range of 0 to 150 °C. Figure 8The dielectric loss of polymer samples I-1, I-2, I-3 and I-4 is shown in Figure 2. It can be seen that the dielectric loss is kept below 0.02 at 10 Hz in the range of 0 to 150 °C.

[0117] Electrochemical performance tests were performed on the electrodes prepared based on the above Examples 1-4, as shown below.

[0118] Electrical energy storage performance test: The polymer film (I-1, I-2, I-3, I-4) plated with electrodes was placed in a ferroelectric instrument equipped with an environmental chamber for electrical polarization energy storage performance test. The temperature of the environmental chamber was set at 150°C. The electric field strength applied to the test sample was accumulated at 50MV / m. The electric field strength and electric displacement curve were derived in each accumulation process until the sample was electrically broken down. The energy storage density and charge and discharge efficiency were calculated by integrating the electric field strength and electric displacement curve.

[0119] Continuous charge and discharge cycle test: The polymer (I-1, I-2, I-3, I-4) film plated with electrodes was placed in a capacitance tester equipped with an environmental chamber for charge and discharge cycle test. The temperature of the environmental chamber was set at 150°C. An electric field with a frequency of 1Hz and an intensity of 350MV / m was applied to the test sample. The test sample was cycled continuously for 10,000 times. The oscilloscope outputted the storage and discharge density, and calculated the charge and discharge efficiency each time.

[0120] like Fig. 9 The charge-discharge diagrams of polymer samples I-1, I-2, I-3 and I-4 show that at 150°C, only a low electric field strength of 350 MV / m is required to obtain a charge-discharge rate of about 10.8 J / cm 3 The electric polarization energy storage density (charge and discharge efficiency>90%) indicates that it has high energy storage density and energy storage efficiency.

[0121] like Fig.10 The charge-discharge cycle diagram of polymer samples I-1, I-2, I-3 and I-4 shows that they can be continuously and stably charged and discharged for nearly 50,000 times under an electric field of 350 MV / m, and the polymer dielectric film is not broken down. After multiple experimental tests, the maximum polarization energy storage density of polymer (I) of the present invention increases from 17.5 J / cm to 27.5 J / cm when n is less than 500 as n increases from 200 to 500. 3 Increased to 21.4 J / cm 3 , the charge and discharge efficiency of the maximum energy storage density increased from 88% to 92%, and the continuous charge and discharge performance increased from 10.5J / cm 3 and 92% increased to 10.8 J / cm 3 When n exceeds 500, the maximum polarization energy storage density, the charge-discharge efficiency of the maximum energy storage density, and the continuous charge-discharge performance do not increase further.

[0122] In summary, the polymer of the present invention is obtained by ring-opening metathesis polymerization of norbornene pyrrolidine monomer initiated by Grubbs catalyst, and the crystal lattice shows anisotropy from the high-resolution transmission electron microscope image, which proves the formation of ferroelectric microstructure. This ferroelectric microstructure increases the net dipole moment of the polymer and improves the dielectric constant. In particular, when the temperature exceeds the glass transition temperature of the polymer, the polarization motion volume of the phenylsulfone group in the ferroelectric microstructure increases, further increasing the dielectric constant. At the same time, due to the presence of ferroelectric crystals, the overall thermal stability of the polymer is maintained, so that the polymer maintains low dielectric loss. The increased dielectric constant and low dielectric loss enable the polymer to exhibit high electric polarization energy storage density at high temperature. The polymer film prepared by the present invention has the characteristics of transparency, flexibility, easy processing, high glass transition temperature, high thermal conductivity, high dielectric constant, low dielectric loss, high energy storage density and high energy storage efficiency, and exhibits stable electrostatic energy storage characteristics at 150°C.

[0123] Although specific embodiments of the present invention are described above, those skilled in the art should understand that these are merely examples and that various changes or modifications may be made to the embodiments without departing from the principles and essence of the present invention. The scope of protection of the present invention is limited only by the appended claims.

Claims

1. A high temperature dielectric polymer, characterized in that The polymer has the general formula shown in formula (I): Wherein n represents the number of repeating structural units, and n is an integer greater than 200.

2. The method for preparing a high temperature dielectric polymer according to claim 1, characterized in that: The steps include: S1. reducing 5-norbornene-2,3-dicarboximide with lithium aluminum tetrahydride to obtain a 5-norbornene-pyrrolidine intermediate; S2. 5-norbornene-pyrrolidine and p-toluenesulfonyl chloride are placed in a chloroform solution, and triethylamine is added dropwise to react to obtain norbornene-pyrrolidine phenylsulfone monomer; S3. The norbornene pyrrolidine phenyl sulfone monomer is subjected to a ring-opening metathesis polymerization reaction using a Grubbs catalyst under anhydrous and oxygen-free conditions. After terminating the reaction, the polymer product is diluted, settled, washed, and dried to obtain polynorbornene pyrrolidine phenyl sulfone; S4. Place polynorbornene pyrrolidine phenyl sulfone and p-toluenesulfonyl hydrazide in a toluene solution and subject the mixture to a hydrogenation reaction to obtain a polymer of formula (I).

3. The method for preparing a high temperature dielectric polymer according to claim 2, characterized in that: In step S3, the solvent for the ring-opening metathesis polymerization reaction is N,N-dimethylformamide, and the Grubbs catalyst is 3-phenyl-1H-indene-1-ylidene[bis(isobutylphosphine ligand)]ruthenium(II) dichloride.

4. The method for preparing a high temperature dielectric polymer according to claim 2, characterized in that: In step S3, the molar ratio of the norbornene pyrrolidine phenyl sulfone monomer to the Grubbs catalyst is (200-500):1; and / or the concentration of the norbornene pyrrolidine phenyl sulfone monomer is 0.05-0.1 mol / L.

5. The method for preparing a high temperature dielectric polymer according to claim 2, characterized in that: In step S3, the conditions for the ring-opening metathesis polymerization reaction are: a temperature of 30 to 50° C.; and / or a reaction time of 1 to 2 hours.

6. The method for preparing a high temperature dielectric polymer according to claim 2, characterized in that: In step S3, the terminator of the ring-opening metathesis polymerization reaction is vinyl ethyl ether.

7. The method for preparing a high temperature dielectric polymer according to claim 2, characterized in that: In step S4, the hydrogenation reaction temperature conditions are: temperature 120° C.; and / or reaction time 3 to 6 hours.

8. A method for preparing a thin film using the high temperature dielectric polymer described in claim 1, characterized in that: The steps include: A1. The polymer of formula (1) is dissolved in N,N-dimethylformamide to obtain a film-forming solution; A2. After the film-forming liquid is evenly coated on the glass sheet, the solvent is evaporated at 25-40°C in advance, and then it is completely dried under vacuum at 80-100°C to obtain a transparent flexible film, and finally annealed at 200-250°C.

9. The method for preparing a thin film according to claim 8, characterized in that: The concentration of the membrane-making solution is 3-5 wt %.

10. Use of the high temperature dielectric polymer according to claim 1 in an electrostatic energy storage insulating material.

Citation Information

Patent Citations

  • Cross-linkable high dielectric norbornene copolymer and norbornene cross-linked polymer and preparation methods thereof

    CN104693423A

  • Norbornene zwitterionic monomer and preparation method thereof

    CN109535062A

  • High-temperature electrostatic energy storage double-chain structure polymer dielectric medium and preparation method thereof

    CN113087879A

  • Porous polypyrrolidine material as well as preparation method and application thereof

    CN116284694A

  • Norbornene-based polymer having low dielectric constant and low-loss properties and insulating material using the same

    US20100210803A1